1995
DOI: 10.1016/s1078-5884(05)80116-9
|View full text |Cite
|
Sign up to set email alerts
|

Preferential use of vein for above-knee femoropopliteal grafts

Abstract: The demand for vein for secondary procedures is low. Amputation rates when vein grafts do occlude are half those of PTFE and amputation level is significantly influenced by graft type. We advocate preferential use of vein in above-knee femoropopliteal bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Wilson et al make an effective argument against preferential use of prosthetic grafts. 10 They examined their series of 112 above-knee femoropopliteal bypass grafts and concluded that the 3-year results were superior for autogenous vein, that the amputation rate after graft failure was significantly higher when Gore-tex was used, and that the secondary vein was only rarely needed after Gore-tex failure. The strong evidence that small-diameter grafts have a greater risk of occlusion is counterintuitive.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al make an effective argument against preferential use of prosthetic grafts. 10 They examined their series of 112 above-knee femoropopliteal bypass grafts and concluded that the 3-year results were superior for autogenous vein, that the amputation rate after graft failure was significantly higher when Gore-tex was used, and that the secondary vein was only rarely needed after Gore-tex failure. The strong evidence that small-diameter grafts have a greater risk of occlusion is counterintuitive.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a great deal of research work has focused on developing biodegradable polymeric 390 L. Ye et al / Journal of Biomaterials Science 22 (2011) [389][390][391][392][393][394][395][396][397][398][399][400][401][402][403][404][405][406] scaffolds with mechanical properties appropriate for application in the vascular tissue engineering [3]. However, in small-diameter arterial replacements, TE vascular grafts often fail due to their unsatisfactory patency resulting from early thrombosisrelated occlusion caused by imperfect endothelium layers [2,[4][5][6]. How to maintain long-term patency of these small-diameter vascular grafts remains a significant challenge in vascular tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to some authors reporting results with the use of prosthetic graft being equivalent to the use of autologous vein graft, [7][8][9][10] and because others advocated the use of autologous vein both for above and below knee (BK) arterial reconstruction. 11,12 Otherwise, for infrageniculate arterial bypass, the opinion that autologous vein is the best conduit is widely accepted. 13,14 However, patients with arteriosclerosis obliterans (ASO) can suffer from potential ischemic heart disease (IHD) concomitantly and they need to undergo some interventional coronary angioplasty and/ or coronary bypass surgery.…”
Section: Introductionmentioning
confidence: 99%